Pharmacological Differences between Native Homomeric Transient Receptor Potential Canonical Type 4 Channels and Heteromeric Transient Receptor Potential Canonical Type 1/4 Channels in Lateral Septal Neurons - Kevin D. Phelan; U Thaung Shwe; Fang Zheng (MDPI AG, 2023)
Given the unique expression patterns and revelations of its critical involvement in a host of neurological disorders, the TRPC1/4/5 subgroup has become an intense target of drug development, and some compounds are now in clinical trials. However, little is known about the exact subunit composition of this subfamily of TRPC channels in various native tissues, and whether it has functional and pharmacological implications. In this study, we investigated the effects of two TRPC4 modulators located in the lateral septum, in which a metabotropic glutamate receptor (mGluR) agonist-induced plateau potential is mediated by TRPC channels composed of TRPC1 and TRPC4. Lateral septal neurons were recorded intracellularly in brain slices using sharp electrodes. Drugs were applied via bath superfusion. We showed that the plateau potential in mice lacking TRPC1 is modulated by ML204 and La3+ in a manner that is like homomeric TRPC4 channels in artificial expression systems. However, the plateau potential that is primarily mediated by heteromeric TRPC1/4 channels in lateral septal neurons in wildtype mice was modulated differently by ML204 and La3+. Our data suggest that native homomeric TRPC4 channels and heteromeric TRPC1/4 channels are pharmacologically distinct, and the current drug development strategy regarding TRPC1/4/5 may need to be reevaluated.